Human Resource Management Strategy in Multinational Companies in Indonesia - Cahyati, Tetet; Sahlan, Muhammad; Nuratri, Bangkit; Ahmad, Asep Zulkifli (Universitas Negeri Makassar, 2024)
Multinational companies operating in Indonesia face complex challenges in managing human resources due to diverse cultural, regulatory, and economic factors. In response, companies must implement strategic human resource management (HRM) practices that align with both global standards and local demands. This research aims to explore the HRM strategies employed by multinational companies in Indonesia and analyze their effectiveness in enhancing organizational performance and employee engagement. Using a qualitative research approach, in-depth interviews were conducted with HR managers from various multinational firms across different sectors. Data were collected to gain insights into the strategies used to address challenges such as talent acquisition, employee retention, cross-cultural management, and regulatory compliance. The data were analyzed using thematic analysis, focusing on identifying common patterns and unique approaches in HRM practices. The findings reveal that successful HRM strategies in these companies are characterized by adaptability, a strong emphasis on leadership development, and a commitment to fostering an inclusive work environment. Moreover, the integration of local knowledge with global HRM frameworks was found to be a key factor in overcoming the challenges specific to Indonesia’s business landscape. This study provides practical insights for HR practitioners and policymakers in multinational firms, offering a framework for developing HRM strategies that improve both employee satisfaction and organizational competitiveness in Indonesia’s dynamic market.